Adsorption performance of coconut shell activated carbon for the removal of chlorate from chlor-alkali brine stream - Lakshmanan, S. (IWA Publishing, 2016)
Activated carbon from coconut shell was used to investigate the adsorption of chlorate from a chloralkali plant's brine stream. The effect of pH, flowrate, chlorate and chloride concentration on the breakthrough curves were studied in small-scale column trials. The results obtained show enhanced adsorption at low flowrates, higher chlorate concentrations, and at a pH of 10. These studies show that introducing an activated carbon adsorption column just before the saturator would remove sufficient quantities of chlorate to allow more of the chlor-alkali plant's brine stream to be reused. From column dynamic studies, the Thomas model showed close approximation when the chlorate in the effluent was higher than breakthrough concentrations and there was close correlation at high influent concentration. The qo (maximum adsorption capacity) values were close to those obtained experimentally, indicating close representation of the breakthrough curve by the Thomas model. Â© IWA Publishing 2016.